Public Services in Good Governance - Tavares, Andre Da Costa (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Public services in good governance must at least meet the quality that must be met. The provision of public services is very important in encouraging good governance practices in Timor-Leste. Therefore, professional public services need to be realized in government governance with a good service delivery system. Implementation of good governance in government, community and private service providers can be carried out with innovative service activities and still paying attention to the principles of good governance. This research aims to determine public services to support good governance practices using quantitative methods with a descriptive analytical approach. This research was conducted on 30 Timor Leste Ministry of Health staff using the saturation (census) method. Data was collected by distributing questionnaires and analysis techniques using Simple Linear Regression analysis. The T test results show that there is significant public service impact on good governance so that improvements in public services are needed to support more efficient and transparent governance.